Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1074/jbc.m112.345876
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Specific Recognition of Rpt1p, an ATPase Subunit of 26 S Proteasome, by Proteasome-dedicated Chaperone Hsm3p

Abstract: Background: Hsm3 is a proteasome-dedicated chaperone that forms a base precursor, Hsm3-Rpt1-Rpt2-Rpn1. Results: Crystal structures of Hsm3 and Hsm3-Rpt1 were determined. Conclusion: The Hsm3-Rpt1 interface is formed by a hydrophobic core and complementary charged interactions and is important for the proteasome assembly. Significance: The study provides the structural basis for the assembly mechanism of the base subcomplex of the 26 S proteasome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Chaperone binding is thus hypothesized to occlude contacts between the Rpt tail and its cognate a pocket, thus minimizing the formation of premature or incorrect RP-CP contacts ). The RP chaperones Hsm3, Nas6, and Rpn14 do not bind the Rpt tail, only the proximal C domain Takagi et al 2012). Thus, they may occlude the tail by virtue of the proximity of the C domain to the tail.…”
Section: Rp Assemblymentioning
confidence: 99%
“…Chaperone binding is thus hypothesized to occlude contacts between the Rpt tail and its cognate a pocket, thus minimizing the formation of premature or incorrect RP-CP contacts ). The RP chaperones Hsm3, Nas6, and Rpn14 do not bind the Rpt tail, only the proximal C domain Takagi et al 2012). Thus, they may occlude the tail by virtue of the proximity of the C domain to the tail.…”
Section: Rp Assemblymentioning
confidence: 99%
“…The subunits of the RP base can be expressed in E. coli as soluble proteins. The reconstituted RP base confers an equivalent activity to the 26S proteasomes than the endogenous complex [98,99].…”
Section: Molecular Composition Of the Rp Basementioning
confidence: 99%
“…Moreover, the crystal structure of RAC4 revealed that it has a C-shaped structure consisting of 11 HEAT repeats. 38 The structure of the RAC4−Rpt1−C complex revealed that the interacting surface between RAC4 and Rpt1 is a hydrophobic core and complementary charged surface. Mutations in the RAC4−Rpt1 surface resulted in an assembly defect in the 26S proteasome.…”
Section: Assemblymentioning
confidence: 99%